2018
DOI: 10.1177/000313481808400672
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pharmacologic Prevention of VTE in Trauma: IMPACT-IT QI Project

Abstract: Enoxaparin regimens commonly used for prophylaxis fail to achieve optimal anti-factor Xa levels in up to 70 per cent of trauma patients. Accordingly, trauma services at the study institution endeavored to develop a standardized approach to optimize pharmacologic prevention with enoxaparin. An enoxaparin venous thromboembolism (VTE) prophylaxis protocol implemented in October 2015 provided weight-adjusted initial dosing parameters with subsequent dose titration to achieve targeted anti-factor Xa levels. Symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Overall, the results support that using anti-Xa levels to guide LMWH dosing is effective in reducing the overall rate of VTE, consistent with much of the existing literature. 4,[16][17][18][19] Although this study involved thousands of patients, it was still limited by sample size. Because of the low incidence of PE events in the population, the sample size must be exceedingly large to detect small but potentially clinically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the results support that using anti-Xa levels to guide LMWH dosing is effective in reducing the overall rate of VTE, consistent with much of the existing literature. 4,[16][17][18][19] Although this study involved thousands of patients, it was still limited by sample size. Because of the low incidence of PE events in the population, the sample size must be exceedingly large to detect small but potentially clinically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Research in the trauma surgery population generally supports the notion that VTE rates are reduced when anti-Xa levels are in range. 4,[16][17][18][19] However, other studies have not confirmed this relationship, finding no improvement in VTE rates despite in-range anti-Xa levels. [20][21][22] The variability in study outcomes may be explained by small study populations coupled with a very small incidence of VTE rates overall.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The use of anti-Xa assay (to measure plasma heparin; UFH and LMWH)-guided thromboprophylaxis is promising for reducing VTE occurrence in trauma patients. [ 30 ] Future studies of anti-Xa-directed therapy (as opposed to prophylaxis) may provide evidence for reassurance in terms of bleeding risk.…”
Section: Discussionmentioning
confidence: 99%